The mispriced ADRs of Allied Irish Bank - Jacob, Joshy, (SAGE Knowledge. Cases., 2017)
In early 2014, it appeared to some observers that investors in the American Depository Receipts (ADRs) of Allied Irish Bank (AIB) were not aware that the ADR now represented only 3.5 shares of AIB and not 10 shares. These observers suggested that certain Irish (and American) market participants cant add up. Moreover, these observers suggested that the underlying shares in Ireland were themselves overvalued, and therefore the ADR was doubly overvalued. The roots of all these issues went back to the nationalization of AIB during 2008-2011 which left only a tiny free float of privately held shares outstanding.